PEMODELAN ZONA KESTABILAN LERENG PADA DAERAH PUNCAK PASS, MEGAMENDUNG, DAN SEKITARNYA, KABUPATEN BOGOR, JAWA BARAT - Setianto Setiawan, David
Natural disasters are a phenomenon that often occurs around us. One of phenomenon that often occurs is landslide. In 2017 until mid-2018, there were 14 reports of landslide occurred in Bogor Regency. The research area is in Puncak Pass area, Megamendung, and its surroundings. The purpose of this research is model slope-stability map to classify zones or areas of slope susceptibility to landslides. The method that is used to analyze slope-stability is using TRIGRS program. This program analyzes slope-stability that are influenced by infiltration of rain into the soil. Inputs that are entered into this program are slope data, water flow direction data, rainfall data, and the physical and mechanical properties of the soil. Data is processed by infinite slope-stability analysis and then used to build slope-stability model. The output of this program is a grid-based slope stability map that can be classified to determine slope-stability zones against the occurrence of the landslide Slope Stability Model divided into 4 slope stability zone, i.e. Very Stable Zone, Stable Zone, Less Stable Zone, and Unstable Zone. The result of the model shows that Very Stable Zone occupies in 31%, Stable Zone occupies in 5%, Less Stable Zone occupies 13%, and Unstable Zone occupies 51% of research area. The slope stability map is conformed according to the condition on 9 February 2019 when a major landslide occurred on 5 February 2019